Transforming Doppler tomography to unravel the accretion dynamics in cataclysmic variables - Kotze, Enrico Juan (Department of Astronomy, 2017)
Doppler tomography has revolutionised the interpretation of phase-resolved spectra of interacting binaries. The standard technique extracts emission and kinematic information contained in such spectra and projects it onto a two-dimensional velocity coordinate frame. This thesis describes my investigation of constructing Doppler tomograms in 'inside-out' coordinates by reversing the velocity axis. The aim was to determine if the emission distribution in the inside-out tomogram is more intuitive to interpret than the standard tomogram, and if it reveals indiscernible or enhances less discernible details. The inside-out tomogram is constructed by projecting the spectra onto the inside-out coordinate frame with zero velocity transposed to the outer circumference and the maximum velocities to the centre of the tomogram. In addition, this thesis describes a new flux modulation mapping technique applied to the standard and inside-out Doppler tomography of magnetic cataclysmic variables. I developed this technique with the aim to obtain more information from their observed spectra and present it in a useful format. It extracts the flux modulation from consecutive half-phase tomograms and constructs maps of the amplitude and phasing characteristics of the modulation in these systems. My investigation, involving the spectra of non-magnetic and magnetic cataclysmic variables, shows that the inside-out projection redistributes the relative contrast levels in and amongst the emission components. The inside-out projection exposes low-velocity emission details which are overly compacted and enhances high-velocity emission details which are overly tenuous in the standard projection. In addition, the flux modulation mapping technique gives a significant improvement in reproducing the input spectra adding more confidence in the interpretation of the modulation maps. Notable results were obtained for the polars where the blob-like low-velocity emission in their standard tomograms is more exposed in their inside-out tomograms, making it easier to distinguish between the ballistic and magnetic accretion flows that are evident in their trailed spectra. Also, for all the polars investigated the high-velocity magnetic accretion flows not seen in their standard tomograms are revealed in their inside-out tomograms. This extra information is extremely valuable to form a more complete picture of the emission components, broadening our knowledge of the accretion dynamics in these systems.